Acute GVHD prophylaxis plus ATLG after myeloablative allogeneic haemopoietic peripheral blood stem-cell transplantation from HLA-identical siblings in patients with acute myeloid leukaemia in remission: final results of quality of life and long-term outcome analysis of a phase 3 randomised study. Issue 2 (February 2019) - Bonifazi, Francesca; Solano, Carlos; Wolschke, Christine; Sessa, Mariarosaria; Patriarca, Francesca; Zallio, Francesco; Nagler, Arnon; Selleri, Carmine; Risitano, Antonio Maria; Messina, Giuseppe; Bethge, Wolfgang; Herrera, Pilar; et al.
Summary: Background: We previously showed that human anti-T-lymphocyte globulin (ATLG) plus ciclosporin and methotrexate given to patients with acute leukaemia in remission, having allogeneic haemopoietic stem-cell transplantation with peripheral blood stem cells from an HLA-identical sibling donor after myeloablative conditioning, significantly reduced 2-year chronic graft-versus-host disease (cGVHD) incidence and severity, without increasing disease relapse and infections, and improves cGVHD-free and relapse-free survival (cGRFS). The aim of an extended follow-up study was the assessment of long-term outcomes, which are, in this context, scarcely reported in the literature. We report unpublished data on quality of life (QoL) from the original study and the results of a follow-up extension. Methods: In the original open-label study, patients with acute myeloid and lymphoblastic leukaemia in first or subsequent remission, having sibling HLA-identical allogeneic peripheral blood stem-cell transplantation, were randomly assigned (1:1) to receive ATLG plus standard GVHD prophylaxis with ciclosporin and short-term methotrexate (ATLG group) or standard GVHD prophylaxis without ATLG (non-ATLG group). Conditioning regimens were cyclophosphamide 120 mg/kg with either total body irradiation (12 Gy) or busulfan (12·8 mg/kg intravenously or 16 mg/kg orally), with or without etoposide (30–60 mg/kg). Randomisation was stratified according to centre and disease risk. The primary endpoint was cumulative incidence of cGVHD at 2 years. The primary and secondary endpoints, excluding QoL, have been published. QoL, assessed using European Organisation for Research and Treatment of Cancer QLQ-C30 and QLQ-HDC29 questionnaires, was an unpublished secondary endpoint, which we now report here. A follow-up extension was then done, with the primary endpoint cumulative incidence of cGVHD. Enrolment has been completed for both studies. The original trial (number, NCT00678275 ) and follow-up extension (number, NCT03042676 ) are registered atClinicalTrials.gov . Findings: In the original study, from Dec 14, 2006, to Feb 2, 2012, 161 patients were enrolled and 155 were randomly assigned to either the ATLG group (n=83) or to the non-ATLG group (n=72). In the follow-up study, which started on Feb 7, 2017, and was completed on June 30, 2017, 61 patients were included in the ATLG group and 53 were included in the non-ATLG group. Global health status showed a more favourable time course in the ATLG group compared with the non-ATLG group (p=0·02; treatment by visit interaction). ATLG was descriptively superior to non-ATLG at 24 months for physical function (points estimate −14·8 [95% CI −26·4 to −3·1]; p=0·014) and social function (–19·1 [–38·0 to −0·2]; p=0·047), gastrointestinal side-effects (8·8 [2·5–15·1]; p=0·008) and effect on family (13·5 [1·2–25·8]; p=0·032). Extended follow-up (median 5·9 years [IQR 1·7–7·9]) confirmed a lower 5-year cGVHD incidence (30·0% [95% CI 21·4–41·9] vs 69·1% [59·1–80·1]; analysis for entire follow-up, p<0·001), no increase in relapses (35·4% [26·4–47·5] vs 22·5% [14·6–34·7]; p=0·09), improved cGRFS (34·3% [24·2–44·5] vs 13·9% [7·1–22·9]; p=0·005), and fewer patients still in immunosuppression (9·6% vs 28·3%; p=0·017) in the ATLG group compared with the non-ATLG group. 5-year overall survival, relapse-free survival, and non-relapse mortality did not differ significantly between groups. Interpretation: The addition of ATLG to standard GVHD prophylaxis improves the probability of surviving without disease relapse and cGVHD after myeloablative peripheral blood stem-cell transplantation from an HLA-identical sibling donor for patients with acute leukaemia in remission. Further additional benefits are better QoL and shorter immunosuppressive treatment compared with standard GVHD prophylaxis without ATLG. Therefore, in this setting, ATLG plus standard GVHD prophylaxis should be preferred over the standard GVHD prophylaxis alone. Funding: Neovii Biotech.